2017
DOI: 10.1002/jctb.5492
|View full text |Cite
|
Sign up to set email alerts
|

Lipase production by solid‐state fermentation of olive pomace in tray‐type and pressurized bioreactors

Abstract: BACKGROUND Bioreactor type, sterilization and specific operational conditions are key factors for the scale‐up of solid‐state fermentation (SSF). This work deals with the lipase production by SSF of olive pomace (OP) in traditional tray‐type and pressurized bioreactors. Important aspects of SSF in bioreactors were studied, such as the need for sterilization and moisture content (MC) control. RESULTS At larger scale, there was no significant difference in lipase production between sterilized and unsterilized su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…and Galactomyces sp. are likely to be strongly involved in phenol biodegradation (Supplementary Material 2), which agrees with several previous works (Pinedo-Rivilla et al, 2009;Alves et al, 2014;Karimi and Hassanshahian, 2016;Oliveira et al, 2018). The identified bacterial species revealed that Lactobacillus acidipiscis was the agent most correlated with phenolic and lipid biodegradation (Supplementary Material 2), which was previously identified in a work recently done by Uylaşer and Yildiz (2014) and has been identified as a halophilic lactic acid bacterium able to tolerate up to 8% NaCl from black and green olive samples, representing almost 28% of the total identified genus.…”
Section: Changes In Microbial Community Structure Duringsupporting
confidence: 91%
“…and Galactomyces sp. are likely to be strongly involved in phenol biodegradation (Supplementary Material 2), which agrees with several previous works (Pinedo-Rivilla et al, 2009;Alves et al, 2014;Karimi and Hassanshahian, 2016;Oliveira et al, 2018). The identified bacterial species revealed that Lactobacillus acidipiscis was the agent most correlated with phenolic and lipid biodegradation (Supplementary Material 2), which was previously identified in a work recently done by Uylaşer and Yildiz (2014) and has been identified as a halophilic lactic acid bacterium able to tolerate up to 8% NaCl from black and green olive samples, representing almost 28% of the total identified genus.…”
Section: Changes In Microbial Community Structure Duringsupporting
confidence: 91%
“…Differences in enzymes production relatively to the quantity of dry macroalgae may be due, at least in part, to the higher aeration, mass and heat transfer in tray bioreactor compared to flasks (Khanahmadi et al, 2018). On the other hand, the increase of solids loading can limit the production of enzymes if the bed height is increased (Oliveira et al, 2018), which was not the case of the experiments of this work, since similar height beds were used in both trays (2.5 cm) and it was not observed an increase of temperature in the bed during SSF. The need to sterilize the substrate hinders the scale-up of SSF, therefore it was studied the fermentation of macroalgae in tray type bioreactor without sterilization of substrate.…”
Section: Scale-up Of Enzymes Production In Tray-type Bioreactorsmentioning
confidence: 99%
“…Among filamentous fungi species used in SSF Aspergillus ibericus has been proved to be promising. It is "generally regarded as safe" (GRAS) (Oliveira et al, 2018), whose hyphal growth mode allows it to efficiently penetrate in the substrate, thus efficiently growing under SSF conditions, and it has potential to produce cellulases and xylanases (Salgado et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“… Network visualization map for the co-occurrence of works that bring information about the scale-up process using lipases applied to bioprocesses [ 41 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 ]. Publications in the period from 2018 to 2022 were considered.…”
Section: Figurementioning
confidence: 99%